Food sovereignty on the northwestern coast of Ecuador Food sovereignty on the northwestern coast of Ecuador (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
The research consisted of identifying the spaces of traditional uses for food security and sovereignty, as well as learning about traditional gastronomy and understanding the mandates of the elders on the importance of rationally managing natural resources for collective well-being in communities located in the upper basin of the Cayapas River, Telembí parish, Eloy Alfaro canton, northwestern coast of Ecuador. The methodology applied was qualitative, using bibliographic review, semi-structured interview techniques and focus groups. The sample included 60 male and female producers and leaders from 10 communities (37% of the universe), applying gender and generational approaches. As a result, it was observed that the inhabitants manage natural resources in close relation to the concept of peasant family agriculture, which responds to the cosmovision and productive practices of ancestral communities. These populations struggle to conserve their territory, sustain the agrifood system to guarantee food security and sovereignty, in a context of antagonism between local actors and hegemonic economic groups (agroindustrial capitalism). The communities have clearly identified and manage their traditional uses for food production (hills, canoeras, cantero, forest and river), which have been sustained for more than 300 years in the territory. The way and the reasons for preparing food are linked to daily events, festivals and rituals, allowing the strengthening of traditions through gastronomy. The teaching mechanisms of the elders have contributed to recovering, strengthening, repositioning and reconstructing the existence of the communities as an ancestral right.